Answer:
8
Step-by-step explanation:
6 x 9=54. 54+10=64. the square root of 64 = 8
Answer:
12
Step-by-step explanation:
Since this is a right triangle, we can use trig functions
cos theta = adj / hyp
cos 60 = 6/hyp
hyp = 6 / cos 60
hyp = 6 / (1/2)
htp = 12
Answer:
c
Step-by-step explanation:
Answer:
Step-by-step explanation:instead, try making the subscripts and superscripts stand out:
n-1
a = a * r
n n-1
Believe me, it's worth the extra work to do this!!
Given the sequence -3, -6, -12, -24, you can easily see that the first term,
a is -3. The common factor is 2. Note how (-3)*2=-6, and so on.
1
So, a = -3 and r=2.
1
So the formula for this geometric sequence is
n-1
a = -3*2
n
Answer:
2nd option
Step-by-step explanation: